2008
DOI: 10.1179/joc.2008.20.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Profile of Contemporary Clinical Strains ofStenotrophomonas maltophiliaIsolates: Can Moxifloxacin Activity Be Predicted by Levofloxacin MIC Results?

Abstract: The susceptibility profile of 763 Stenotrophomonas maltophilia isolates was evaluated against 16 antimicrobials by the CLSI reference broth microdilution method. Minocycline (MIC(90), 1 microg/ml; 100.0% susceptible) was the most active compound, followed by doxycycline (MIC(90), 4 microg/ml; 99.6% susceptible), trimethoprim/sulfamethoxazole (MIC(90), 1 microg/ml; 97.8% susceptible), and tigecycline (MIC(90), 2 microg/ml). An excellent correlation between levofloxacin (MIC(90), 4 microg/ml; 86.5% susceptible b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
2
9
0
1
Order By: Relevance
“…No isolates were resistant to minocycline. This data was similar to that of Taiwan, Brazil, Spain, and the USA 5,15-17. MICs of tigecycline ranged from 0.25 to 8 µg/mL, and MIC 50 and MIC 90 were 1 and 2 µg/mL, respectively, which were similar to those in other studies 1,11.…”
supporting
confidence: 89%
“…No isolates were resistant to minocycline. This data was similar to that of Taiwan, Brazil, Spain, and the USA 5,15-17. MICs of tigecycline ranged from 0.25 to 8 µg/mL, and MIC 50 and MIC 90 were 1 and 2 µg/mL, respectively, which were similar to those in other studies 1,11.…”
supporting
confidence: 89%
“…Levofloxacin and moxifloxacin have good in vitro activity against S. maltophilia, especially moxifloxacin, which has lower MIC values against S. maltophilia than earlier quinolones [35]. In the present study, although the susceptibility rates were a little lower than some previous studies [1], these two drugs demonstrated good in vitro activity.…”
Section: Discussionmentioning
confidence: 65%
“…The tetracycline derivatives minocycline and tigecycline have shown good in vitro activity against clinical isolates of S. maltophilia [3]. Previous studies in Taiwan, Brazil, Spain, and the USA showed that there was no or low resistance to tigecycline [3202122]. However, this study showed that 11.9% of clinical 118 S. maltophilia complex isolates displayed resistance to tigecycline.…”
Section: Discussionmentioning
confidence: 88%
“…This rate was much higher than the rate in previous studies, although the patient group in this study did not include patients with cystic fibrosis who usually show high resistance rates to TMP/SMX according to previous studies. The resistance rate to levofloxacine was 30.5%, which was higher than the rates of 3 to 13% seen in a previous studies [3121314202122]. The tetracycline derivatives minocycline and tigecycline have shown good in vitro activity against clinical isolates of S. maltophilia [3].…”
Section: Discussionmentioning
confidence: 90%